A method of manufacturing a low rolling resistance polyurethane drive wheel
Patent Information
- Application Number
- CN202610650922.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-12
- Publication Date
- 2026-09-29
AI Technical Summary
[0003]然而,现有制造方法存在一个被长期忽视的深层次问题:预热过程中轮芯与模具的温度场不匹配
1.界面结合强度显著提高,连续的硬度梯度结构完全消除了界面处的残余应力,同时化学键合和机械互锁共同作用,使界面结合强度较现有技术大幅提高,有效防止了早期脱胶问题。
Smart Images

Figure CN122830033A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material molding and processing technology, specifically to a method for manufacturing a low rolling resistance polyurethane drive wheel. Background Technology
[0002] Polyurethane drive wheels are widely used in AGV / RGV handling systems, semiconductor cleanrooms, panel production lines, and amusement facilities. Their performance directly affects equipment operating efficiency, load-bearing capacity, and service life. Current technology for manufacturing polyurethane drive wheels mainly includes wheel core pretreatment, mold preheating, polyurethane casting, curing and demolding, and post-processing. The goals of low rolling resistance, high load-bearing capacity, and low wear are achieved by optimizing material formulations and improving processing precision.
[0003] However, existing manufacturing methods suffer from a long-overlooked, deep-seated problem: the temperature field mismatch between the wheel core and the mold during preheating. Current technology typically heats the wheel core and mold to the same temperature before casting, assuming this ensures uniform polyurethane curing. However, in reality, the heat capacity and thermal conductivity of the wheel core and mold differ significantly. Even with the same initial temperature, an uneven temperature gradient forms during casting and curing, causing residual stress at the polyurethane interface, leading to decreased interfacial adhesion and premature debonding.
[0004] More importantly, this temperature gradient also leads to the formation of randomly distributed microbubbles and uneven density regions within the polyurethane, causing periodic elastic deformation fluctuations in the wheel during rolling, significantly increasing rolling resistance. Simultaneously, these micro-defects become the starting point for wear, accelerating wheel wear and generating more dust particles in cleanroom environments. Existing technologies typically address these issues by extending preheating time, increasing vacuum levels, or adding post-curing processes. However, these methods not only increase production costs and cycle time but also fail to fundamentally eliminate the effects of temperature field mismatch and may even introduce new defects. Therefore, this paper provides a method for manufacturing a low-rolling-resistance polyurethane drive wheel to overcome the aforementioned problems. Summary of the Invention
[0005] The purpose of this invention is to provide a method for manufacturing a low rolling resistance polyurethane drive wheel to solve the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the present invention provides a method for manufacturing a low rolling resistance polyurethane drive wheel, including wheel core pretreatment, mold preheating, mixture preparation, casting and curing, demolding and finishing steps, and performing surface gradient modification treatment on the wheel core to form an amino functional group film on the surface of the wheel core that only reacts chemically with the high-temperature curing agent. The modified wheel core and the matching mold were preheated separately to stabilize the temperature difference between the surface of the wheel core and the inner wall of the mold at 20±1℃. A temperature-responsive mixture was prepared, comprising polycaprolactone diol prepolymer, composite curing agent, temperature-triggered nucleating agent, in-situ microbubble regulator, silane coupling agent KH550, and negative pressure-induced nucleating agent. The mixture is injected into a preheated mold and subjected to negative pressure self-assembly gradient curing to form a continuous hardness gradient structure from the wheel core side to the mold side and a three-dimensional microchannel network that runs through the interior of the material.
[0007] Furthermore, the gradient modification treatment of the wheel core surface specifically involves immersing the sandblasted steel wheel core in an ethanol solution of 5% KH550 silane coupling agent at 80°C for 15 minutes, then drying it at 120°C for 30 minutes to form an amino functional group film with a thickness of 50 to 80 nm; the surface roughness of the wheel core is controlled between Ra3.2 and Ra6.3 μm.
[0008] Furthermore, the differentiated preheating specifically involves preheating the modified wheel core at 132°C for 80 minutes and preheating the matching mold at 112°C for 50 minutes. After preheating, the temperature of the wheel core surface and the inner wall of the mold is measured at no less than 5 measurement points using an infrared thermometer, and the average value is taken to confirm the temperature difference.
[0009] Furthermore, the composite curing agent is composed of 3,3'-dichloro-4,4'-diaminodiphenylmethane and isophorone diamine in a molar ratio of 7:3. By mass, 100 parts of polycaprolactone diol prepolymer corresponds to 6 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane and 2 parts of isophorone diamine.
[0010] Furthermore, the temperature-triggered nucleating agent is a nano-zinc oxide whisker with a stearic acid-modified surface and an aspect ratio of 15:1, with an addition amount of 0.4 parts by mass; the negative pressure-induced nucleating agent is a hollow glass microsphere with an amino-modified surface, a particle size of 5 to 10 μm, and a wall thickness of 1 μm, with an addition amount of 0.2 parts by mass.
[0011] Furthermore, the in-situ microbubble regulator is an azodicarbonamide microcapsule with paraffin as the wall material, a melting point of 119°C, and a particle size of 20 to 30 μm, and the addition amount is 0.35 parts by weight.
[0012] Furthermore, the preparation of the temperature-responsive mixture specifically involves heating the polycaprolactone diol prepolymer to 82°C, adding nano-zinc oxide whiskers and hollow glass microspheres, and stirring at 1500 r / min for 8 minutes; then adding the composite curing agent and azodicarbonamide microcapsules, and continuing to stir for 2 minutes; then degassing under a vacuum of 0.098 MPa for 3 minutes, controlling the viscosity of the mixture to be between 1000 and 1500 mPa·s.
[0013] Furthermore, the negative pressure self-assembly gradient curing specifically involves injecting the mixture into the mold at a uniform speed of 60 g / s, followed by curing at 121°C for 90 minutes. The curing process involves four sequential reactions: Within 0 to 20 minutes, the temperature on the wheel core side rises to over 130°C. 3,3'-dichloro-4,4'-diaminodiphenylmethane reacts with amino functional groups to form a hard segment enriched interface layer with a thickness of 0.8 to 1.2 mm, resulting in a volume shrinkage of 0.8 to 1.2% and the formation of a negative pressure field of 0.02 to 0.03 MPa. In 20 to 30 minutes, the internal temperature of the material reaches 119°C. The azodicarbonamide microcapsules melt and decompose to produce nitrogen gas. Under the guidance of the negative pressure field and the induction of nano zinc oxide whiskers, a chain-like microbubble structure arranged in the radial direction is formed with hollow glass microspheres as nodes. In 30 to 50 minutes, the chain-like microbubbles connect with each other to form a three-dimensional microchannel network with a diameter of 60 to 90 μm and a spacing of 150 to 200 μm; For 50 to 90 minutes, the temperature on the mold side is maintained at around 112°C. The isophorone diamine reaction forms a soft segment enriched wear-resistant surface layer with a thickness of 1.5 to 2 mm, forming a continuous hardness gradient from Shore A95 to Shore A82.
[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. The interfacial bonding strength is significantly improved. The continuous hardness gradient structure completely eliminates the residual stress at the interface. At the same time, the combined effect of chemical bonding and mechanical interlocking greatly improves the interfacial bonding strength compared with the existing technology, effectively preventing early debonding problems.
[0015] 2. Rolling resistance is significantly reduced. The three-dimensional microchannel network can uniformly distribute the stress during the rolling process. At the same time, the microporous structure absorbs elastic deformation energy and avoids periodic deformation fluctuations, resulting in a significant reduction in rolling resistance compared to existing technologies.
[0016] 3. Significantly improved wear resistance and cleanliness: The surface layer enriched with soft segments has excellent self-lubricating properties, while the microchannel network can store a small amount of wear debris, avoiding abrasive wear and greatly reducing wear compared to existing technologies; the three-dimensional microchannel network has a strong adsorption capacity, which can actively capture tiny dust particles generated by wear and prevent them from spreading into the air, significantly reducing dust emissions compared to existing technologies, making it particularly suitable for Class 10 and Class 100 cleanrooms in the semiconductor and panel industries.
[0017] 4. It achieves self-healing function. When a tiny scratch occurs on the surface of the drive wheel, the incompletely cured polyurethane prepolymer stored in the microchannel network will slowly seep out under pressure and temperature, fill the scratch and undergo a curing reaction. It has excellent self-healing efficiency and significantly extends the service life of the drive wheel.
[0018] 5. Excellent dynamic stress adjustment performance: The three-dimensional microchannel network has excellent elasticity and damping characteristics, which can adjust the stress distribution in real time during the rolling process, absorb shock and vibration, and significantly reduce the dynamic stress fluctuation coefficient compared with the existing technology. The drive wheel runs more smoothly at high speed, which significantly improves the positioning accuracy and operation stability of AGV / RGV.
[0019] 6. Production efficiency is greatly improved, the total production cycle is significantly shortened compared to existing technologies, energy consumption is significantly reduced, and there is no need for expensive high-vacuum casting equipment and additional post-curing processes. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of a method for manufacturing a low rolling resistance polyurethane drive wheel according to the present invention. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Please see Figure 1 The present invention provides a technical solution: See Figure 1 An embodiment of a method for manufacturing a low rolling resistance polyurethane drive wheel is shown below: Example
[0023] Raw material formula: by weight: Polycaprolactone diol prepolymer: NCO content 4.8%, molecular weight 2000, 100 parts; Composite curing agent: 6 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane and 2 parts of isophorone diamine, molar ratio 7:3; Temperature-triggered nucleating agent: nano zinc oxide whiskers, surface modified with stearic acid, aspect ratio 15:1, 0.4 parts; In-situ microbubble regulator: azodicarbonamide microcapsules, with paraffin wax as the wall material, melting point 119℃, particle size 20 to 30 μm, 0.35 parts; Silane coupling agent KH550: 0.8 parts Negative pressure induced nucleation agent: hollow glass microspheres with amino-modified surface, particle size 5 to 10 μm, wall thickness 1 μm, 0.2 parts; Raw material pretreatment: Polycaprolactone diol prepolymer was dehydrated in a vacuum oven at 80°C for 2 hours before use, maintaining a vacuum level above 0.098 MPa. 3,3'-dichloro-4,4'-diaminodiphenylmethane was melted at 100°C and held for 30 minutes before use to remove water of crystallization. Isophorone diamine was dried using molecular sieves for 24 hours before use. Nano-zinc oxide whiskers and hollow glass microspheres were dried at 120°C for 4 hours before use to remove surface-adsorbed moisture. Azodicarbonamide microcapsules were sealed and stored at room temperature before use to prevent premature decomposition due to heat.
[0024] Manufacturing equipment: The manufacturing equipment used in this embodiment includes: a CNC lathe G80, a thermal drying oven HKO3S, a planetary mixer, a vacuum degassing machine, a casting machine CPU20JN5, an infrared thermometer, a hardness tester, a universal testing machine, a rolling resistance tester, an abrasion tester, a dust concentration tester, and a dynamic stress analyzer.
[0025] Manufacturing steps: Step 1: Gradient modification treatment of wheel core surface: The sandblasted steel wheel core was placed in an ultrasonic cleaner and cleaned with anhydrous ethanol for 10 minutes to remove surface oil and sandblasting debris. After cleaning, the wheel core was removed and dried with compressed air. Then, the wheel core was immersed in an 80°C ethanol solution of silane coupling agent KH550 (5% by mass) for 15 minutes. During immersion, the solution temperature was kept constant, and the solution was gently stirred every 5 minutes to ensure full contact between the wheel core surface and the solution. After immersion, the wheel core was removed and dried in a 120°C thermal drying oven for 30 minutes. After drying, a 50-80 nm thick amino functional group film was formed on the wheel core surface. This film only reacts chemically with the high-temperature curing agent 3,3'-dichloro-4,4'-diaminodiphenylmethane, and does not react chemically with the low-temperature curing agent isophorone diamine, laying the foundation for subsequent interfacial gradient bonding.
[0026] The surface roughness of the wheel core is controlled between Ra3.2 and Ra6.3 μm. The abrasive used for sandblasting is brown corundum with a particle size of 80 mesh. The sandblasting pressure is 0.4 to 0.6 MPa, the sandblasting distance is 150 to 200 mm, and the sandblasting angle is 45 to 60 degrees. After sandblasting, the surface of the wheel core must be free of oxide scale, oil, and other impurities.
[0027] Step 2: Precise temperature difference preheating: The modified wheel core was placed in the first thermal cycling drying oven, with a preheating temperature of 132℃ and a preheating time of 80 minutes. The matching mold was then placed in the second thermal cycling drying oven, with a preheating temperature of 112℃ and a preheating time of 50 minutes. The drying oven doors were kept closed during preheating to avoid temperature fluctuations. After preheating, the temperature of the wheel core surface and the inner wall of the mold was measured using an infrared thermometer at at least five points, and the average value was taken as the final temperature. The temperature difference between the wheel core surface and the inner wall of the mold was confirmed to be stable within a range of 20±1℃. This temperature difference is the core control parameter for achieving dual-gradient sequential curing, and the error must not exceed ±2℃.
[0028] Before use, the mold should be cleaned by wiping the inner wall and parting surface with anhydrous ethanol to remove residual polyurethane and release agent. Then, apply a layer of high-temperature resistant sealant to the parting surface to prevent leakage during casting. During mold assembly, ensure all components fit tightly, with a coaxiality error not exceeding 0.03mm.
[0029] Step 3: Preparation of temperature-responsive mixtures: The pretreated polycaprolactone diol prepolymer was added to a planetary mixer, heated to 82°C, and held at that temperature. Then, nano-zinc oxide whiskers and hollow glass microspheres were added, and the mixture was stirred at 1500 rpm for 8 minutes. During stirring, the temperature was kept constant to ensure the whiskers and microspheres were uniformly dispersed in the prepolymer, forming temperature-sensitive nucleation points. After stirring, molten 3,3'-dichloro-4,4'-diaminodiphenylmethane and isophorone diamine, along with azodicarbonamide microcapsules, were added, and stirring continued for 2 minutes. Immediately after stirring, the mixture was transferred to a vacuum degassing machine and degassed at 0.098 MPa for 3 minutes. The surface of the mixture was observed during degassing; degassing was stopped when no more bubbles overflowed. At this point, the paraffin wall material of the azodicarbonamide microcapsules had not yet melted and no bubbles were generated.
[0030] The viscosity of the mixture should be controlled between 1000 and 1500 mPa·s. Viscosity should be measured using a rotational viscometer at 82°C. If the viscosity is too high, the stirring temperature can be increased appropriately, but should not exceed 85°C. If the viscosity is too low, the stirring time can be extended appropriately, but should not exceed 10 minutes.
[0031] Step 4: Negative pressure self-assembly gradient curing: The degassed mixture is injected uniformly into a preheated mold at a rate of 60 g / s using a casting machine. During casting, the gating nozzle is kept submerged below the surface of the mixture to prevent air entrapment. Immediately after casting, the casting machine is turned off, and the entire mold is placed in an oven at 121°C for curing for 90 minutes. During this process, a four-stage continuous self-assembly reaction occurs: 1.0 to 20 minutes: The temperature on the wheel core side first rises to above 130°C. 3,3'-dichloro-4,4'-diaminodiphenylmethane reacts with the amino functional groups on the wheel core surface to form a hard segment-rich interface layer with a thickness of 0.8 to 1.2 mm, which chemically bonds with the wheel core. During curing, this layer produces a volume shrinkage of 0.8 to 1.2%, creating a negative pressure field of 0.02 to 0.03 MPa within the uncured mixture.
[0032] 2.20 to 30 minutes: The internal temperature of the material reaches 119℃, the paraffin wall material of the azodicarbonamide microcapsules melts, and the azodicarbonamide decomposes to produce nitrogen gas. Under the guidance of the negative pressure field, the bubbles move towards the wheel core side and, induced by nano-zinc oxide whiskers, self-assemble with hollow glass microspheres as nodes to form a radially arranged chain-like microbubble structure.
[0033] 3.30 to 50 minutes: As the curing reaction proceeds, the negative pressure field gradually intensifies, and the chain-like microbubbles connect with each other, forming a three-dimensional microchannel network that runs through the entire interior of the material. The diameter of the microchannels stabilizes at 60 to 90 μm, and the spacing is 150 to 200 μm.
[0034] 4.50 to 90 minutes: The mold side temperature is maintained at around 112℃, and isophorone diamine begins to react slowly, forming a soft segment-rich wear-resistant surface layer with a thickness of 1.5 to 2 mm. There is no obvious interface between the three layers, forming a continuous hardness gradient, gradually transitioning from Shore A95 in the interface layer to Shore A82 in the surface layer.
[0035] The oven temperature fluctuation during curing must not exceed ±1℃. Record the oven temperature every 15 minutes to ensure it remains stable at the set value. Do not open the oven door during curing to avoid a sudden temperature drop that could affect the curing effect.
[0036] Step 5: Post-curing and finishing: After curing, remove the mold from the oven and place it on a horizontal platform to cool naturally to room temperature for at least 2 hours. Demold after cooling. Use a dedicated demolding tool to avoid damaging the polyurethane layer and wheel core. No additional post-curing process is required after demolding. Mount the drive wheel on a CNC lathe and precision machine the inner hole and end face. The inner hole machining tolerance is H7, the end face runout is no more than 0.02mm, and the outer diameter runout is no more than 0.03mm. After machining, clean the drive wheel surface with anhydrous ethanol to remove cutting debris and oil, then perform a visual inspection and dimensional check.
[0037] Visual inspection requires the polyurethane layer surface to be smooth, free from defects such as bubbles, cracks, missing material, and flow marks. Dimensional inspection uses vernier calipers and micrometers, measuring at no fewer than three points, and the average value is taken as the final dimension. Passing inspection, the drive wheels are packaged and stored. Example
[0038] The difference between this embodiment and Embodiment 1 is that the amount of hollow glass microspheres added is 0.15 parts. The remaining raw material formulation, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Embodiment 1. Example
[0039] The difference between this embodiment and Embodiment 1 is that the amount of hollow glass microspheres added is 0.25 parts. The remaining raw material formulation, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Embodiment 1. Example
[0040] The difference between this embodiment and Embodiment 1 is that the preheating temperature of the wheel core is 130℃, the preheating temperature of the mold is 115℃, and the temperature difference is 15℃. The remaining raw material formula, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Embodiment 1. Example
[0041] The difference between this embodiment and Embodiment 1 is that the preheating temperature of the wheel core is 135℃, the preheating temperature of the mold is 110℃, and the temperature difference is 25℃. The remaining raw material formula, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Embodiment 1.
[0042] Comparative Example 1: Existing conventional methods: Raw material formula: by weight: Polycaprolactone diol prepolymer: NCO content 4.8%, molecular weight 2000, 100 parts Curing agent: 3,3'-dichloro-4,4'-diaminodiphenylmethane, 8 parts Silane coupling agent KH550: 0.8 parts Raw material pretreatment: It is exactly the same as Example 1.
[0043] Manufacturing equipment: It is exactly the same as Example 1.
[0044] Manufacturing steps: 1. Place the sandblasted steel wheel core into an ultrasonic cleaner and clean it with anhydrous ethanol for 10 minutes to remove surface oil and sandblasting debris. After cleaning, remove the wheel core and dry the surface with compressed air. Then immerse the wheel core in an 80℃ silane coupling agent KH550 ethanol solution (5% by mass) for 15 minutes. After immersion, remove the wheel core and dry it in a 120℃ hot circulating drying oven for 30 minutes.
[0045] 2. Place the modified wheel core and matching mold simultaneously into a thermal drying oven and preheat at 120℃ for 60 minutes. After preheating, use an infrared thermometer to confirm that the temperature of both the wheel core and the mold is 120℃.
[0046] 3. Add the pretreated polycaprolactone diol prepolymer to a planetary mixer, heat to 82°C and maintain the temperature. Then add molten 3,3'-dichloro-4,4'-diaminodiphenylmethane and stir at 1500 rpm for 5 minutes. Immediately after stirring, transfer the mixture to a vacuum degassing machine and degas for 5 minutes under a vacuum of 0.098 MPa.
[0047] 4. Pour the degassed mixture into the preheated mold at a uniform speed of 60g / s using a casting machine. Immediately after casting, turn off the casting machine and place the entire mold in an oven at 120℃ for curing for 4 hours.
[0048] 5. After curing, remove the mold from the oven and allow it to cool naturally to room temperature before demolding. After demolding, perform a post-curing treatment at 100℃ for 4 hours. After post-curing, mount the drive wheel on a CNC lathe and perform precision machining on the inner hole and end face. After machining, perform visual inspection and dimensional verification.
[0049] Comparative Example 2: Lacking hollow glass microspheres: The difference between this comparative example and Example 1 is that hollow glass microspheres are not added to the raw material formulation. The remaining raw material formulation, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Example 1.
[0050] Comparative Example 3: The wheel core and the mold are preheated at the same temperature: The difference between this comparative example and Example 1 is that the wheel core and the mold are preheated simultaneously at 122°C for 60 minutes, with a temperature difference of 0°C. The remaining raw material formulation, raw material pretreatment, manufacturing equipment, and manufacturing steps are exactly the same as in Example 1.
[0051] Comparative Example 4: Single Curing Agent: The difference between this comparative example and Example 1 is that the composite curing agent used is 3,3'-dichloro-4,4'-diaminodiphenylmethane, with a dosage of 8 parts. The remaining raw material formulations, raw material pretreatments, manufacturing equipment, and manufacturing steps are exactly the same as in Example 1.
[0052] Performance testing and comparative analysis: The polyurethane drive wheels prepared in the above embodiments and comparative examples were subjected to performance tests. All tests were conducted under a standard environment of 23±2℃ and 50±5% relative humidity. Three parallel samples were prepared for each test item, and the average value of the test results was taken.
[0053] Test items and test methods: 1. Interface Bond Strength Test: A universal testing machine was used for the test, following the standard GB / T16585-1996, "Determination of Bond Strength between Vulcanized Rubber and Metal—Tensive Method". The specimen was a cylindrical specimen with a diameter of 25 mm and a thickness of 10 mm, with a metal wheel core diameter of 10 mm. The tensile speed was 50 mm / min, and the maximum tensile force at specimen failure was recorded. The interface bond strength was then calculated.
[0054] 2. Rolling Resistance Coefficient Test: The test is conducted using a rolling resistance testing machine, following the standard GB / T18861-2012 "Automobile Tire Rolling Resistance Test Method - Load Method". The test load is 500 N, the test speed is 1 m / s, and the test time is 10 minutes. The average resistance during the test is recorded, and the rolling resistance coefficient is calculated.
[0055] 3. Abrasion Test: The Akron abrasion tester was used for testing, and the test standard was GB / T1689-2014 "Determination of Abrasion Resistance of Vulcanized Rubber (Akron Abrasion Tester Method)". The test load was 26.7 N, the test speed was 2.84 m / s, and the test distance was 1.61 km. The mass of the sample was weighed before and after the test, and the abrasion amount was calculated.
[0056] 4. Dust Emission Test: A dust concentration meter was used for the test, which was conducted in a sealed test chamber with a volume of 1 m³. The test load was 500 N, the test speed was 1 m / s, and the test time was 30 minutes. The average concentration of PM0.1 in the chamber during the test was recorded as the dust emission.
[0057] 5. Self-healing performance test: A 0.3mm deep and 10mm long scratch was made on the surface of the drive wheel using a scalpel. The drive wheel was then run at a speed of 1m / s for 1 hour under a 500N load. After the run, the repair of the scratch was observed under a microscope, the remaining depth of the scratch was measured, and the self-healing efficiency was calculated. The self-healing efficiency is equal to the original scratch depth minus the remaining depth, divided by the original scratch depth, and multiplied by 100%.
[0058] 6. Dynamic Stress Fluctuation Coefficient Test: A dynamic stress analyzer was used for the test. Three strain gauges were embedded inside the drive wheel, located at the interface layer, intermediate layer, and surface layer, respectively. The test load was 500 N, the test speed was 1 m / s, and the test time was 10 minutes. The stress change data of the three strain gauges were recorded during the test, and the dynamic stress fluctuation coefficient was calculated. The dynamic stress fluctuation coefficient is equal to the maximum stress minus the minimum stress, divided by the average stress.
[0059] 7. Production cycle test: Record the total time from the start of raw material pretreatment to the end of finished product inspection as the production cycle.
[0060] Test results:
[0061] Test Result Analysis 1. Interfacial Bond Strength: The interfacial bond strength of Example 1 reached 18.6 MPa, an increase of 66.1% compared to Comparative Example 1. This is because the continuous hardness gradient structure completely eliminated residual stress at the interface, and the combined effect of chemical bonding and mechanical interlocking significantly improved the interfacial bond strength. The interfacial bond strength of Comparative Example 3 was only 12.8 MPa, proving that temperature difference preheating is the key to achieving gradient curing. The interfacial bond strength of Comparative Example 4 was 14.5 MPa, proving that the use of composite curing agent plays an important role in improving interfacial bond strength.
[0062] 2. Rolling resistance coefficient: The rolling resistance coefficient of Example 1 was as low as 0.0082, a reduction of 42.3% compared to Comparative Example 1. This is because the three-dimensional microchannel network can uniformly disperse the stress during rolling, while the microporous structure absorbs elastic deformation energy, avoiding periodic deformation fluctuations. The rolling resistance coefficient of Comparative Example 2 was 0.0098, demonstrating that the ordered microchannel structure induced by hollow glass microspheres plays an important role in reducing rolling resistance. The rolling resistance coefficient of Comparative Example 3 was 0.0125, demonstrating that random microbubbles and density inhomogeneity caused by isothermal preheating significantly increase rolling resistance.
[0063] 3. Wear performance: The wear amount in Example 1 was only 2.1 mg / 1000 r, a reduction of 58.0% compared to Comparative Example 1. This is because the surface layer enriched with soft segments has excellent self-lubricating properties, and the microchannel network can store a small amount of wear debris, preventing abrasive wear. The wear amount in Comparative Example 4 was 3.6 mg / 1000 r, demonstrating that the uniform structure formed by a single curing agent has poor wear resistance.
[0064] 4. Cleanliness Performance: The dust emission of Example 1 was only 12 μg / m³, a 70.0% reduction compared to Comparative Example 1. This is because the three-dimensional microchannel network has a strong adsorption capacity, actively capturing tiny dust particles generated by wear and preventing them from diffusing into the air. This effect has never been achieved in existing technologies and is particularly suitable for Class 10 and Class 100 cleanrooms in the semiconductor and panel industries. The dust emission of Comparative Example 2 was 18 μg / m³, demonstrating that the adsorption capacity of the ordered microchannel network is far superior to that of randomly distributed microporous structures.
[0065] 5. Self-healing performance: The self-healing efficiency of Example 1 reaches 92%, which is the most significant novel technical effect of this invention. When micro-scratches occur on the surface of the drive wheel, the incompletely cured polyurethane prepolymer stored in the microchannel network slowly seeps out under pressure and temperature, filling the scratches and undergoing a curing reaction to achieve self-healing. Comparative Examples 1 and 3 show no self-healing performance, proving that the microchannel network formed by negative pressure self-assembly is the key to achieving the self-healing function. The self-healing efficiency of Comparative Example 2 is only 65%, proving that the continuous microchannel network formed by hollow glass microspheres as nodes plays a decisive role in improving the self-healing efficiency.
[0066] 6. Dynamic Stress Adjustment Performance: The dynamic stress fluctuation coefficient of Example 1 is only 0.03, a 75.0% reduction compared to Comparative Example 1. This is because the three-dimensional microchannel network has excellent elasticity and damping characteristics, enabling it to adjust the stress distribution during rolling in real time and absorb shocks and vibrations. This effect makes the drive wheel more stable during high-speed operation, significantly improving the positioning accuracy and operational stability of the AGV / RGV. The dynamic stress fluctuation coefficient of Comparative Example 4 is 0.08, demonstrating that the uniform structure formed by a single curing agent has an uneven stress distribution, which easily generates vibration and noise.
[0067] 7. Production Efficiency: The production cycle for all embodiments was 3.5 hours, a reduction of 61.1% compared to Comparative Example 1, with energy consumption reduced by more than 35%. This is because the gradient curing process used in this invention eliminates the need for an additional post-curing step, and the vacuum degassing time is also significantly shortened. Comparative Example 1 required 4 hours of curing followed by 4 hours of post-curing, resulting in a total production cycle of up to 9 hours and low production efficiency.
[0068] Optimal Implementation Example: Based on a comprehensive comparison of the performance test results of all embodiments, Embodiment 1 is the optimal embodiment. In Embodiment 1, the amount of hollow glass microspheres added was 0.2 parts, and the temperature difference between the wheel core and the mold was 20°C. Under these conditions, the performance of the drive wheel prepared reached the optimal level. In Embodiment 2, the amount of hollow glass microspheres added was too small, resulting in insufficient continuity of the microchannel network and a decrease in self-healing efficiency and rolling resistance performance. In Embodiment 3, the amount of hollow glass microspheres added was too large, resulting in a slight decrease in the overall strength of the material. In Embodiments 4 and 5, the temperature difference deviated from the optimal value, resulting in an unsatisfactory gradient curing effect and a decrease in various properties.
[0069] Summarize: This invention discovers and utilizes two long-neglected natural phenomena during the curing process: the temperature gradient caused by the temperature difference between the wheel core and the mold, and the volume shrinkage caused by the curing reaction; transforming these two problems into a driving force for building high-performance functional structures.
[0070] This invention precisely controls the temperature difference between the wheel core and the mold to induce a sequential reaction of the composite curing agent, forming a continuous hardness gradient structure and eliminating residual stress at the interface at its source. Existing technologies assume that a temperature difference between the wheel core and the mold leads to uneven curing, thus attempting to heat both to the same temperature. However, in reality, the heat capacity and thermal conductivity of the wheel core and the mold differ significantly, resulting in an uneven temperature gradient during casting and curing even at the same initial temperature. This invention proactively utilizes this temperature gradient, designing a composite curing agent system with different reactivity levels. The high-temperature curing agent reacts preferentially on the wheel core side, while the low-temperature curing agent reacts later on the mold side, thereby forming a continuous hardness gradient. This hardness gradient structure effectively alleviates stress concentration at the interface, completely eliminates residual stress, and significantly improves interfacial bonding strength.
[0071] Simultaneously, this invention utilizes the volume shrinkage generated during interface layer curing to create a negative pressure field within the material, guiding microbubbles to self-assemble into a pervasive three-dimensional microchannel network. Existing technologies consider that microbubbles generated during curing reduce the material's strength and wear resistance, thus attempting to eliminate them by increasing vacuum levels. However, completely eliminating bubbles is impossible, and excessively increasing vacuum levels increases production costs and time. This invention proactively utilizes the negative pressure field generated by curing volume shrinkage, designing a temperature-triggered microbubble regulator and a negative pressure-induced nucleating agent. This allows microbubbles to be generated 20 to 30 minutes after curing begins, aligning radially with hollow glass microspheres as nodes under the guidance of nano-zinc oxide whiskers, and self-assembling into an ordered three-dimensional microchannel network. This microchannel network not only reduces rolling resistance and adsorbs dust but also stores incompletely cured prepolymers, achieving self-healing capabilities and dynamic stress regulation.
[0072] Temperature difference preheating not only induced gradient curing but also provided a suitable temperature field for the decomposition of microbubble regulators. The negative pressure field generated by the volume shrinkage during curing not only guided the self-assembly of microbubbles but also promoted the curing reaction. The three-dimensional microchannel network not only achieved self-healing and dynamic stress regulation but also improved the elasticity and damping properties of the material, further reducing rolling resistance and wear.
[0073] This invention is applicable to various scenarios requiring polyurethane drive wheels, such as AGV / RGV handling systems, semiconductor cleanrooms, panel production lines, and amusement facilities. Particularly in Class 10 and Class 100 cleanrooms in the semiconductor and panel industries, the self-cleaning function of this invention can significantly reduce dust emissions and improve product yield. In AGV / RGV handling systems, the low rolling resistance and high wear resistance of this invention can significantly reduce energy consumption, extend service life, and improve operating efficiency.
Claims
1. A method for manufacturing a low rolling resistance polyurethane drive wheel, comprising the steps of wheel core pretreatment, mold preheating, mixture preparation, casting and curing, and demolding and finishing, characterized in that, A surface gradient modification treatment is performed on the wheel core to form an amino functional group film on the wheel core surface that only reacts chemically with a high-temperature curing agent; The modified wheel core and the matching mold were preheated separately to stabilize the temperature difference between the surface of the wheel core and the inner wall of the mold at 20±1℃. A temperature-responsive mixture was prepared, comprising polycaprolactone diol prepolymer, composite curing agent, temperature-triggered nucleating agent, in-situ microbubble regulator, silane coupling agent KH550, and negative pressure-induced nucleating agent. The mixture is injected into a preheated mold and subjected to negative pressure self-assembly gradient curing to form a continuous hardness gradient structure from the wheel core side to the mold side and a three-dimensional microchannel network that runs through the interior of the material.
2. The manufacturing method of a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The gradient modification treatment of the wheel core surface specifically involves immersing the sandblasted steel wheel core in an ethanol solution of 5% KH550 silane coupling agent at 80°C for 15 minutes, then drying it at 120°C for 30 minutes to form an amino functional group film with a thickness of 50 to 80 nm; the surface roughness of the wheel core is controlled between Ra3.2 and Ra6.3 μm.
3. The manufacturing method of a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The differentiated preheating process involves preheating the modified wheel core at 132℃ for 80 minutes and preheating the matching mold at 112℃ for 50 minutes. After preheating, the temperature of the wheel core surface and the inner wall of the mold is measured at no less than 5 points using an infrared thermometer, and the average value is taken to confirm the temperature difference.
4. The manufacturing method of a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The composite curing agent is composed of 3,3'-dichloro-4,4'-diaminodiphenylmethane and isophorone diamine in a molar ratio of 7:
3. By mass, 100 parts of polycaprolactone diol prepolymer corresponds to 6 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane and 2 parts of isophorone diamine.
5. The manufacturing method of a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The temperature-triggered nucleating agent is a nano-zinc oxide whisker with a stearic acid-modified surface and an aspect ratio of 15:1, with an addition amount of 0.4 parts by mass; the negative pressure-induced nucleating agent is a hollow glass microsphere with an amino-modified surface, a particle size of 5 to 10 μm, and a wall thickness of 1 μm, with an addition amount of 0.2 parts by mass.
6. The method for manufacturing a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The in-situ microbubble regulator is azodicarbonamide microcapsules with paraffin as the wall material, a melting point of 119℃, and a particle size of 20 to 30 μm, and the addition amount is 0.35 parts by weight.
7. The manufacturing method of a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The specific preparation of the temperature-responsive mixture involves heating the polycaprolactone diol prepolymer to 82°C, adding nano-zinc oxide whiskers and hollow glass microspheres, and stirring at 1500 r / min for 8 minutes; then adding the composite curing agent and azodicarbonamide microcapsules, and continuing to stir for 2 minutes; then degassing under a vacuum of 0.098 MPa for 3 minutes, controlling the viscosity of the mixture between 1000 and 1500 mPa·s.
8. The method for manufacturing a low rolling resistance polyurethane drive wheel as described in claim 1, characterized in that: The negative pressure self-assembly gradient curing process specifically involves injecting the mixture into a mold at a uniform speed of 60 g / s and then curing it at 121°C for 90 minutes. The curing process involves four sequential reactions: Within 0 to 20 minutes, the temperature on the wheel core side rises to over 130°C. 3,3'-dichloro-4,4'-diaminodiphenylmethane reacts with amino functional groups to form a hard segment enriched interface layer with a thickness of 0.8 to 1.2 mm, resulting in a volume shrinkage of 0.8 to 1.2% and the formation of a negative pressure field of 0.02 to 0.03 MPa. In 20 to 30 minutes, the internal temperature of the material reaches 119°C. The azodicarbonamide microcapsules melt and decompose to produce nitrogen gas. Under the guidance of the negative pressure field and the induction of nano zinc oxide whiskers, a chain-like microbubble structure arranged in the radial direction is formed with hollow glass microspheres as nodes. In 30 to 50 minutes, the chain-like microbubbles connect with each other to form a three-dimensional microchannel network with a diameter of 60 to 90 μm and a spacing of 150 to 200 μm; For 50 to 90 minutes, the temperature on the mold side is maintained at around 112°C. The isophorone diamine reaction forms a soft segment enriched wear-resistant surface layer with a thickness of 1.5 to 2 mm, forming a continuous hardness gradient from Shore A95 to Shore A82.